(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
An agronomical trial on Napier fodder was conducted to determine the biomass yield and chemical composition with the effect of different sources of organic manures such as biogas slurry, broiler litter and layer litter for fodder production. There was significant (P<0.05) difference in biomass yield and chemical composition among different treatment groups. The maximum biomass yield (mt/ha) was observed in layer litter (16.67a± 0.89) followed by Broiler litter (10.05bc ± 0.10), Biogas slurry (08.97bc± 0.99) and control group (06.65c± 0.90; respectively. It also showed that number of tiller/hill was significantly (P≤0.05) differed among the treatments and maximum observed in layer litter (19.50a ± 1.05) than others. The DM% in all groups was mostly similar but DM yield was the highest (19.11± 0.44%)) in layer litter compared to others group. It may be suggested that layer litter may be used as organic sources of fertilizer as well as the soil health and fodder cultivation for small to large scale farmers in Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 128-131